LESSON PLANS FOR TEACHING ENGLISHTO YOUNG LEARNERS :A CASE STUDY OF LESSON PLANS OF TWO ELEMENTARY SCHOOLSIN BANDUNG KULON, WEST JAVA - Astri Rejeki, - (2009)
An effective instruction is indicated by designing lesson plan well. The lesson plans should be suitable to the students' characteristics and needs. Using qualitative methods with descriptive case study as its framework, three teachers' lesson plans of two different elementary schools in Bandung Kulon were analyzed using theories that were adapted from Reiser and Dick (1996) and Cameron (2002). The data were gained from documentation and interview. The three teacher' lesson plans under study showed that the aspects taken into their lesson plans might contradict what were expected. It seemed there was still a gap between each aspect of the lesson plans, if they should meet the students' characteristics. It is an indication that the teachers need improvement of how to formulate lesson plans properly.